Italy : Background Economic Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This paper focuses on selected aspects of Italy's fiscal situation, its origins, and its pervasive economic consequences. The paper analyzes different aspects of regional duality and the unbalanced recovery. The paper highlights that regional duality is a salient feature of the Italian economy. In the south, average incomes and consumption are lower, unemployment rates higher, and the percentage of the population living in poverty larger than in the center and north. The paper also examines fiscal performance of Italy during 1986-95.